320 Phase IIa study of alpha-DC1 vaccine against HER2/HER3, chemokine modulation regimen and pembrolizumab in patients with asymptomatic brain metastasis from triple negative or HER2+ breast cancer. (10th December 2020) - Gandhi, Shipra; Forsyth, Peter; Opyrchal, Mateusz; Ahmed, Kamran; Khong, Hung; Attwood, Kristopher; Levine, Ellis; O'Connor, Tracey; Early, Amy; Fenstermaker, Robert; Prasad, Dheerendra; Takabe, Kazuaki; et al.
Abstract : Background: Brain metastases develop in up to 50% patients with metastatic triple negative breast cancer (TNBC) and HER2+ BC and are an increasing source of morbidity and mortality. HER3, overexpressed in triple negative and HER2+ brain metastatic breast cancer (BMBC), is a resistance factor to HER2-targeted therapies and a driver of CNS metastasis. Disease progression is associated with loss of anti-HER2/3 immunity. We have demonstrated that alphaDC1 loaded with glioma-specific peptides induce intratumoral production of chemokines (CXCL9, CXCL10, CXCL11, CCL5) which attract CXCR3- and CCR5- expressing cytotoxic T-lymphocytes (CTLs) and T-helper 1 (Th1) cells to brain tumors, inducing clinical responses and long-term disease stabilization in patients with aggressive recurrent primary brain tumors. Our preclinical data show that Chemokine modulating (CKM) regimen [rintatolimod, interferon (IFN)-α2b and COX-2 inhibitor] also selectively attracts effector CTLs and Th1 cells (but not suppressive regulatory T-cells or myeloid-derived suppressor cells) into tumors. Importantly, CKM preferentially promotes CTL migration into tumor rather than healthy tissues, providing rationale for its systemic use. We hypothesize that anti-HER2/3 type 1 polarized DC1s in combination with CKM and anti-PD1 will result in improved Th1/CTL response against HER2/3 epitopes, reduce brain recurrence and systemic progression. Methods: This is a phase II single-arm, non-randomized multicenter study (NCT04348747 ). Eligibility includes patients with triple negative and HER2+ BMBC ≥ 18 years, ECOG PS ≤ 1, normal marrow and organ function with asymptomatic untreated brain metastases who receive αDC1 q2 weeks x 3, with CKM [200 mg IV rintatolimod, IFN-α 20 million units/m2 IV, celecoxib 200 mg oral BID] on days 1-3 with second and third dose of αDC1, followed by pembrolizumab 200 mg IV. Thereafter, pembrolizumab is given every 3 weeks, along with αDC1 and CKM every 3 months as booster dose until disease progression, intolerable side effects or withdrawal from study, or up to 24 months. Baseline and 3-week post-CKM treatment peripheral (non-CNS) biopsies are required for six patients. Primary objective is CNS response rate (RR) using RANO-BM criteria. If no CNS response is observed after 12 patients, study will be terminated. If ≥ 1 response observed, then 9 more patients will be enrolled, for a total of 21 patients. If ≥ 3 CR observed, the proposed therapy will be considered promising for further study. Secondary objectives include non-CNS RR per RECIST v1.1, median CNS, non-CNS and overall progression-free survival, overall survival and safety. Analysis of change in intratumoral biomarkers is an exploratory objective. Results: N/A Conclusions: N/A Trial Registration: NCT04348747 Ethics Approval: The study was approved by Roswell Park Comprehensive Cancer Center Institution's Ethics Board, approval number I-19-04120.